Social and economic rights and liberty: A problematic analysis - Poyanco Bugueño, Rodrigo (Derecho Público Iberoamericano, 2016)
In this article, we will address legal doctrine’s criticism against the relationship between classical liberal constitutionalism, social justice, and positive liberty. We will try to determine to what extent a constitutional judge can intervene directly in these issues and what are the consequences of underestimating the assumptions of classic constitutionalism.